STRATEGY AND TYPE OF RELATIVE CLAUSE IN KLATEN JAVANESE - Maharsi Sri Wigati; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
Relative clauses are essential for updating specific nouns or pronouns that can be used as explanatory meanings. This research is to study the use of markers "sik" and "kang" in the Javanese language in Klaten. The method in this study is descriptive qualitative. The data extraction technique is the skilful free-reference, while the data analysis technique is recorded analysis and note. The results of this study reveal that the relative marking language indicated by particles "sik" and "kang" uses a composition of relative clause constituents in VO type that can be used to allow the arrangement pattern of main constituents - relative clauses. Javanese language in Klaten is also included in the VO type. The basic strategy of forming its relative clause by placing main constituents in front of relative clauses or relative clauses related to relative markers consists of particles "sik" and "kang". This particle is called a ligature which functions as a connective.